Maximum entropy estimation of the Galactic bulge morphology via the VVV Red Clump. Issue 3 (18th May 2020) - Coleman, B; Paterson, D; Gordon, C; Macias, O; Ploeg, H
ABSTRACT: The abundance and narrow magnitude dispersion of Red Clump (RC) stars make them a popular candidate for mapping the morphology of the bulge region of the Milky Way. Using an estimate of the RC's intrinsic luminosity function, we extracted the three-dimensional density distribution of the RC from deep photometric catalogues of the VISTA Variables in the Via Lactea (VVV) survey. We used maximum entropy-based deconvolution to extract the spatial distribution of the bulge from Ks -band star counts. We obtained our extrapolated non-parametric model of the bulge over the inner 40° × 40° region of the Galactic centre. Our reconstruction also naturally matches on to a parametric fit to the bulge outside the VVV region and inpaints overcrowded and high extinction regions. We found a range of bulge properties consistent with other recent investigations based on the VVV data. In particular, we estimated the bulge mass to be in the range [1.3, 1.7]× 10^10 M_, the X-component to be between 18 per cent and 25 per cent of the bulge mass, and the bulge angle with respect to the Sun–Galactic centre line to be between 18° and 32°. Studies of the Fermi Large Area Telescope (LAT) gamma-ray Galactic centre excess suggest that the excess may be traced by Galactic bulge distributed sources. We applied our deconvolved density in a template fitting analysis of this Fermi– LAT GeV excess and found an improvement in the fit compared to previous parametric-based templates.